Association of Eating Behaviour With Diet, Body Weight and Psychological Symptoms in Pregnant Women With Overweight or Obesity - Liimatainen, Elisa (My University, 2025)
Maternal obesity and excessive gestational weight gain (GWG) are related to various complications during pregnancy and adverse effects on the long-term health of both mother and child. Eating behaviour may be an important mediating factor linking unhealthy dietary intake and psychological symptoms to weight gain, yet this phenomenon during pregnancy is not elucidated. This study aimed to distinguish eating behaviour profiles in pregnant women with overweight or obesity using three eating behaviour dimensions, Cognitive restraint, Uncontrolled eating and Emotional eating, and to investigate their associations with diet quality, GWG, body composition and depressive and anxiety symptoms during pregnancy. Women (n = 434) completed the 18-item Three-Factor Eating Questionnaire (TFEQ-R18), three-day food diaries, Index of Diet Quality, Edinburgh Postnatal Depression Scale and Symptom Checklist-90 questionnaires in early and late pregnancy. The body composition was measured by air displacement plethysmography. Confirmatory factor analyses were performed to ensure the factor validity of the TFEQ-R18. Four derived eating behaviour profiles were Struggling, Susceptible, Rational and Easy-going. The profiles were significantly associated with dietary patterns, intakes of energy-yielding nutrients, weight, fat mass and depression and anxiety scores. Changes in eating behaviour dimensions differed significantly between the profiles during pregnancy. Also, significant correlations were found between the dimensions and diet quality, energy intake, pre-pregnancy BMI, fat percentage and GWG. The findings suggest that the eating behaviour profiles could differentiate pregnant women with overweight or obesity predisposed to unfavourable health risks in relation to diet, adiposity and psychological well-being, offering valuable information to consider at maternity clinics.
Keywords: Eating Behaviour, Diet Quality, Dietary Pattern, Gestational Weight Gain, Adiposity, Depression, Anxiety.